Rancang Bangun Otomatisasi Rumah Berbasis Wireless Sensor Network Menggunakan Protokol Komunikasi Message Queuing Telemetry Transport - Muhammad Yusuf Rizaldi; Erwin Susanto; Junartho Halomoan (Jurnal Rekayasa Elektrika, 2018)
Home electronic devices, such as lights, fans, and etcetera are now an inseparable part from the daily life of current society. However, these devices are often used in a wasteful manner. A room light, for example, is often still lit even though it is no longer used. Therefore, a home automation system that can help users to monitor and switch their electronic devices remotely through a user interface must be designed. This research resulted in the design of home automation systems using Wireless Sensor Networks (WSN) which were used to switch the electronic devices and communicate with the user interface. Communication between WSN and the user interface was regulated through the Message Queuing Telemetry Transport (MQTT) protocol. The results of this study were a design of home automation systems that can switch electronic devices remotely with an average delay performance of 0.509 seconds. The quality of the designed WSN was classified as "good" using the Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON) standards, where the round-trip time (RTT) gateway with a latency value was 16.452 ms, jitter was 6.618 ms, and packet loss was 0%.